Antioxidant Activity of Lotion From Sonneratia caseolaris Leaves and Trigona sp. Propolis Extract - Safitri, Annisa Nurul; Kustiawan, Paula Mariana (Biofarmasetikal Tropis (The Tropical Journal of Biopharmaceutical), 2024)
Daily activities can trigger free radicals due to air pollution and increase the decline in skin health. One of the prevention efforts by using a lotion that made from natural ingredients. Natural ingredients such as Sonneratia caseolaris leaves and Trigona sp. bee propolis are still limited used in the form of lotion combination preparations. The purpose of this study was to explore the antioxidant activity of a combination lotion of S. caseolaris leaves and Trigona sp. bee propolis. Antioxidant activity was detemine by used the DPPH technique with lotion formula combination of S. caseolaris leaves and Trigona sp. bee propolis. F1 (1:1), F2 (2:1) and F3 (1:2) accompanied by a physical stability test of the lotion. The results showed that preparations F1, F2, F3 had strong antioxidants in the concentration range of 60-100 ppm. The three formulas met the criteria for a stable lotion preparation. The combination lotion formula has potential in the development of cosmetic products from natural ingredients.